The Effect of Chemical Pretreatment Process on Mechanical Properties and Porosity of Cellulose Bacterial Film - Tito Arif Sutrisno; Heru Suryanto; Retno Wulandari; M. Muhajir; S.M.Shahrul N.S. Zahari (Universitas Negeri Malang, 2019)
Bacterial cellulose (BC) is a natural polymer which have superior properties, like high porosity, high purity, and high permeability. The study objective is to determine the influence of chemical pretreatment on tensile strength and the porosity of BC. The method was to make BC films from pineapple peel extract through fermentation process for 14 days. The pretreatment was conducted by immersion of BC in BmimCl, H2O2, and NaOH solution with a concentration of 2.5%; 5%; and 7.5 %, heated at 80 °C then dried in the oven, and the samples were then tested by a tensile test using ASTM-D636-V standard, morphology analysis using Scanning Electron Microscope, and porosity analysis. The results indicate that the tensile strength of control sample was 123 MPa, whereas after chemical pretreatment, the tensile strength was decreased with the greater reduction occurred using NaOH pretreatment compared than the other solutions that having a lower tensile strength of 8.54 MPa at 7.5 % of NaOH. The results of porosity show that the value increased after being treated chemically. The BC film porosity was 87.13% after NaOH treatment of 7.5% while BC film untreated had porosity of 19.15%. This phenomenon was occurred due to the increasing pore, so the absorption of water increased.